Prevalence of Hyperuricemia among People of Morang District of Nepal (Journal of Nobel Medical College, 2014)
Hyperuricemia refers to an elevation in the serum uric acid concentration. The blood levels of uric acid are a function of the balance between the breakdown of purines & the rate of uric acid excretion. Theoretically, alterations in this balance many account for hyperuricemia. Prolonged hyperuricemia often associated with gout, is an important risk factor for damaged joints. The present study is undertaken with the aim to find out the prevalence of hyperuricemia by age & sex, to establish the statistically significant correlation between serum creatinine & triglyceride concentration with uric acid concentration & to study the relation between alcohol drinking & hyperuricemia in Morang District, by routine health examinations in the out Patients Department (OPD) of Nobel Medical College, Biratnagar from January 2012 to January 2013. The study reveals that 28.57% (male – 30.06%., female -26.61%) of patients have been suffering from hyperuricemia. It indirectly indicates hyperuricemia is very frequent in developing country like Nepal. The present study denoted that hyperuricemia is directly related to alcohol consumption in both male & female. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10048 Journal of Nobel Medical College Vol.3(1) 2014; 16-21